Perceived workplace stressors and professional experiences of clinical embryologists working in Italy and Spain: a pilot qualitative study - Astro, Giancarlo; Gatti, Monica; Costa, Mauro; Cosmelli, Arianna; Alteri, Alessandra; Anastasi, Attilio; Cimadomo, Danilo; Santis, Lucia De; Klinger, Francesca Gioia; Licata, Emanuele; Fernandez, Laura Sosa; Tomasi, Giovanna; et al. (Frontiers in Public Health, 2025)
IntroductionThe well being of clinical embryologists remains a largely neglected aspect in the field of reproductive medicine, despite their critical role in the success of medically assisted reproduction (MAR) procedures. Embryologists manage complex tasks that require high precision and involve significant responsibilities, ranging from manual laboratory procedures to quality control and patient communication. This study aimed to investigate the perceptions of clinical embryologists regarding their occupational well being and to examine their subjective experiences within MAR centers.MethodsQualitative interview study of 28 Italian and Spanish embryologists working at both public and private centers. Participants were recruited among the Italian Society of Embryology, Reproduction, and Research (SIERR) and the Spanish Association for the Study of Reproductive Biology (ASEBIR) members. The interviews were video-recorded and transcribed. Thematic analysis was utilized to identify the main themes and sub-themes.ResultsThe interviewees were concordant that excessive workload might affect their psychophysical well being, especially in view of a salary perceived as unsatisfactory with respect to the high responsibility and training involved by this job. In general, only public sector senior embryologists reported a manageable workload, proportionate to their salary. A key issue identified was the shortage of qualified embryologists, sometimes replaced with less specialized personnel. This might worsen a work environment often perceived challenging because of complex intra-team dynamics, management of interpersonal relationships, and unclear definition of the roles. A competitive and isolating atmosphere can slow down professional growth and limit positive networking. The participants emphasized the importance of patient counseling for their professional well being, advocating for a more intense interaction with the couples. Finally, an ergonomic laboratory environment, optimized equipment arrangement, access to natural light, and the inclusion of adjacent break rooms appear essential for reducing physical and mental fatigue and enhancing overall well being.DiscussionThis study highlights the need to address embryologists' workload, compensation, and professional well being to improve MAR performance and patient care.